1969
DOI: 10.1139/y69-170
|View full text |Cite
|
Sign up to set email alerts
|

Removal of endogenous and exogenous toxins by a microencapsulated absorbent

Abstract: Three types of microencapsulated activated charcoal were tested. Unlike activated charcoal in the free form, the microencapsulated form did not give off embolizing particles. Heparin-complexed or albumin-coated collodion microencapsulated activated charcoal did not lower the arterial platelet level. Albumin-coated collodion microencapsulated activated charcoal was more efficient than the heparin-complexed form in lowering the blood creatinine level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(40 citation statements)
references
References 0 publications
0
39
1
Order By: Relevance
“…While carrying out research on artificial cells (Chang, 1964), my theoretical analysis showed artificial cells can be the basis of a very simple and inexpensive detoxifier that can be more effective than the standard hemodialyser (Chang, 1966). While continuing with basic research on the other aspects of artificial cells, I spent a major part of my early 15-year research career developing this idea followed by successful clinical trials and routine use in patients (Chang, 1966(Chang, , 1969a(Chang, , 1971d(Chang, , 1973a(Chang, , 1974c(Chang, , 1974h, 1975i, 1976g, 1977b.…”
Section: A Brief Historical Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…While carrying out research on artificial cells (Chang, 1964), my theoretical analysis showed artificial cells can be the basis of a very simple and inexpensive detoxifier that can be more effective than the standard hemodialyser (Chang, 1966). While continuing with basic research on the other aspects of artificial cells, I spent a major part of my early 15-year research career developing this idea followed by successful clinical trials and routine use in patients (Chang, 1966(Chang, , 1969a(Chang, , 1971d(Chang, , 1973a(Chang, , 1974c(Chang, , 1974h, 1975i, 1976g, 1977b.…”
Section: A Brief Historical Overviewmentioning
confidence: 99%
“…Thus, Professor Kolff, the inventor of the artificial kidney, wrote the Canadian Medical Research Council that this approach should be extensively supported. Locally, McGill's human ethics committee having reviewed in detail all our preclinical safety and efficacy animal studies (Chang, 1969a(Chang, , 1972aChang and Malave, 1970;Chang et al, 1971a) approved the use of this device for clinical trials at McGill's teaching hospitals. At that time this was a very new idea, and although physicians were very supportive, they were concerned about liability and thus not ready to carry out this procedure in clinical trials in patients.…”
Section: Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The problems of blood compatibility and particle emboli have been largely overcome by microencapsulation with nylon, methacrylate, or cellulose nitrate (22)(23)(24), and hemoperfusion over microencapsulated charcoal has been effective in the clinical management of the uremic syndrome (25). Drugs such as acetylsalicyclic acid, acetaminophen, barbiturates, and glutethimide, which show some protein binding, have also been removed from plasma in vitro (26,27) and in vivo (28)(29)(30)(31)(32) by this technique.…”
Section: Introductionmentioning
confidence: 99%